Allele-specific marker-based assessment revealed that the rice blast resistance genes Pi2 and Pi9 have not been widely deployed in Chinese indica rice cultivars - Tian, Dagang (Rice (N Y), 2016)
BACKGROUND: The most sustainable approach to control rice blast disease is to develop durably resistant cultivars. In molecular breeding for rice blast resistance, markers developed based on polymorphisms between functional and non-functional alleles of resistance genes, can provide precise and accurate selection of resistant genotypes without the need for difficult, laborious and time-consuming phenotyping. The Pi2 and Pi9 genes confer broad-spectrum resistance against diverse blast isolates. Development of allele-specific markers for Pi2 and Pi9 would facilitate breeding of blast resistant rice by using the two blast resistance genes. RESULT: In this work, we developed two new markers, named Pi9-Pro and Pi2-LRR respectively, targeting the unique polymorphisms of the resistant and susceptible alleles of Pi2 and of Pi9. The InDel marker Pi9-Pro differentiates three different genotypes corresponding to the Pi2/Piz-t, Pi9 and non-Pi2/Piz-t/Pi9 alleles, and the CAPS marker Pi2-LRR differentiates the Pi2 allele from the non-Pi2 allele. Based on the two newly developed markers and two available markers Pi2SNP and Pi9SNP, the presence of Pi2 and Pi9 was assessed in a set of 434 rice accessions consisting of 377 Chinese indica cultivars/breeding materials and 57 Chinese japonica cultivars/breeding materials. Of the 434 accessions tested, while one indica restorer line Huazhan was identified harboring the Pi2 resistance allele, no other rice line was identified harboring the Pi2 or Pi9 resistance alleles. CONCLUSIONS: Allele-specific marker-based assessment revealed that Pi2 and Pi9 have not been widely incorporated into diverse Chinese indica rice cultivars. Thus, the two blast resistance genes can be new gene sources for developing blast resistant rice, especially indica rice, in China. The two newly developed markers should be highly useful for using Pi2 and Pi9 in marker-assisted selection (MAS) breeding programs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12284-016-0091-8) contains supplementary material, which is available to authorized users.